Optimization of Business Decision Accuracy through the Application of Mathematical Economics - Ardanta, M Arya; Fauzi, Achmad; Pitri Patimah; Fayza Khadijah; Yeremia Todo Sihombing; Fadia Salma Hasan; Rahmawati, Dinda (International Journal of Advanced Multidisciplinary, 2024)
In the dynamic landscape of contemporary business environments, the need for precise decision-making has become paramount for organizational succes. It explores the strategic integration of mathematical economics as a powerful tool for enchancing decision accuracy in business. Mathematical economics, a discipline that combines economic theories with mathematical methodologies, offers a structured framework to model, and analyze a complex business strategy decision. This study delves into a theorical foundations of mathematical economics and investigates it practical applications in real-world business decision-making processes. Through the utilization of mathematical model, optimization techniques, and statistical analyses, businesses can gain insights into market dynamics, resource allocation, and risk assessment. The objective is to establish a systematic approach that aids decision-makers in formulating well-informed strategies, minimizing uncertaintes, and maximizing overall business performance.